Incidence of Tuberculosis Among HIV-Positive Individuals Initiating Antiretroviral Treatment at Higher CD4 Counts in the HPTN 071 (PopART) Trial in South Africa. (1st January 2018) - Bock, Peter; Jennings, Karen; Vermaak, Redwaan; Cox, Helen; Meintjes, Graeme; Fatti, Geoffrey; Kruger, James; De Azevedo, Virginia; Maschilla, Leonard; Louis, Francoise; Gunst, Colette; Grobbelaar, Nelis; et al.
Abstract : Introduction: Antiretroviral treatment (ART) guidelines recommend life-long ART for all HIV-positive individuals. This study evaluated tuberculosis (TB) incidence on ART in a cohort of HIV-positive individuals starting ART regardless of CD4 count in a programmatic setting at 3 clinics included in the HPTN 071 (PopART) trial in South Africa. Methods: A retrospective cohort analysis of HIV-positive individuals aged ≥18 years starting ART, between January 2014 and November 2015, was conducted. Follow-up was continued until 30 May 2016 or censored on the date of (1) incident TB, (2) loss to follow-up from HIV care or death, or (3) elective transfer out; whichever occurred first. Results: The study included 2423 individuals. Median baseline CD4 count was 328 cells/μL (interquartile range 195–468); TB incidence rate was 4.41/100 person-years (95% confidence interval [CI]: 3.62 to 5.39). The adjusted hazard ratio of incident TB was 0.27 (95% CI: 0.12 to 0.62) when comparing individuals with baseline CD4 >500 and ⩽500 cells/μL. Among individuals with baseline CD4 count >500 cells/μL, there were no incident TB cases in the first 3 months of follow-up. Adjusted hazard of incident TB was also higher among men (adjusted hazard ratio 2.16; 95% CI: 1.41 to 3.30). Conclusions: TB incidence after ART initiation was significantly lower among individuals starting ART at CD4 counts above 500 cells/μL. Scale-up of ART, regardless of CD4 count, has the potential to significantly reduce TB incidence among HIV-positive individuals. However, this needs to be combined with strengthening of other TB prevention strategies that target both HIV-positive and HIV-negative individuals.